Pengaruh Konflik Suriah dan Yaman Terhadap Geopolitik Timur Tengah 2011-2018 - Darmawan, Wawan; Cipta, Samudra Eka (Universitas Cokroaminoto Yogyakarta, 2025)
Syria and Yemen are countries that have been hit by prolonged conflict. This conflict occurred because of demands to revolutionize the corrupt government. The demands for revolution in Yemen initially succeeded in overthrowing Ali Al Saleh as president of the country. Instead of the overthrow of Ali Al Saleh, the situation in Yemen became conducive to the opposite, namely a condition where Yemen became a country that lost its political orientation. This is different from Syria where Hafez Assad handed over full military power in order to continue his power so that Syria is still fully controlled by Hafez Assad. This study discusses the comparison of the situations of the two countries during the revolution that occurred in the Middle East.